2020
DOI: 10.1007/s40263-020-00756-y
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis Disease-Modifying Therapy and the COVID-19 Pandemic: Implications on the Risk of Infection and Future Vaccination

Abstract: The coronavirus 2019 (COVID-19) pandemic is expected to linger. Decisions regarding initiation or continuation of diseasemodifying therapy for multiple sclerosis have to consider the potential relevance to the pandemic. Understanding the mechanism of action and the possible idiosyncratic effects of each therapeutic agent on the immune system is imperative during this special time. The infectious side-effect profile as well as the route and frequency of administration of each therapeutic agent should be careful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
121
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(124 citation statements)
references
References 84 publications
1
121
1
1
Order By: Relevance
“…During the COVID-19 pandemic, many neurologists have adopted a cautious approach to treating MS by delaying or stopping DMTs, due to concerns that DMTs may increase the risk of a SARS-CoV-2 infection or the severity of COVID-19. To date, most published data on COVID-19 outcomes in people with MS are based on smaller case series including patients with various DMTs ( Zheng et al, 2020 ). In general, the emerging data seem to suggest that patients treated with DMTs are not at higher risk of contracting SARS-CoV-2 and seem to have similar risks and outcomes to the general population ( Zheng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the COVID-19 pandemic, many neurologists have adopted a cautious approach to treating MS by delaying or stopping DMTs, due to concerns that DMTs may increase the risk of a SARS-CoV-2 infection or the severity of COVID-19. To date, most published data on COVID-19 outcomes in people with MS are based on smaller case series including patients with various DMTs ( Zheng et al, 2020 ). In general, the emerging data seem to suggest that patients treated with DMTs are not at higher risk of contracting SARS-CoV-2 and seem to have similar risks and outcomes to the general population ( Zheng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the mode of action of a DMT for MS, this may lead to different considerations for patient management. Current risk categorizations of DMTs are mostly based on theoretical considerations around the mode of action and the biology of COVID-19 ( Amor et al, 2020 ; Baker et al, 2020b ; Giovannoni et al, 2020 ; Zheng et al, 2020 ). In future, the potential impact of each DMT on SARS-CoV-2 vaccines will need to be considered and may depend on the type of vaccine used ( Zheng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of disease-modifying therapies (DMTs) is considered the most important factor for determining such risk (Brownlee et al, 2020) and there is wide discussion about the opportunity of continuing or stopping DMTs in MS patients with a diagnosis of DMTs could possibly increase the COVID-19 risks in PwMS because of their effects on immune system. Available data suggest that the risk is higher for second-generation DMTs (Zheng et al, 2020;Sormani et al, 2020). On the other side, it has been hypothesized that DMTs could also have a protective effect against COVID-19 because they could modulate the immune response against SARS-CoV-2, one of the factors associated with the clinical severity of COVID-19, and in some cases, they could exert a direct antiviral effect (Baker et al, 2020;Rostami Mansoor and Ghasemi-Kasman, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Some conflicting evidence, however, revealed that most disease-modifying therapies for MS do not particularly target the innate immune system, which confers protection against SARS-CoV-2, and few have any major long-term impact on CD8 T cells to limit protection against Covid-19 [ 8 ]. Some other researchers have also shown that immunosuppressive therapy neither appears to have a significant consequence on infection with SARS-CoV-2 nor seems to marshal a severe disease course in many cases [ 9 , 10 ]. However, it is generally agreed that some drugs, such as interferons, glatiramer acetate, and teriflunomide seem to be safe.…”
Section: Introductionmentioning
confidence: 99%